Clinic-based intervention reduces unprotected sexual behavior among HIV-infected patients in KwaZulu-Natal, South Africa: results of a pilot study. - Cornman, Deborah H; Kiene, Susan M; Christie, Sarah; Fisher, William A; Shuper, Paul A; Pillay, Sandy; Friedland, Gerald H; Thomas, Cyril M; Lodge, Linda; Fisher, Jeffrey D (Journal of acquired immune deficiency syndromes (1999), 2008)
To evaluate the feasibility, fidelity, and effectiveness of a human immunodeficiency virus (HIV) prevention intervention delivered to HIV-infected patients by counselors during routine clinical care in KwaZulu-Natal, South Africa.
Keywords: Adult; CD4 Lymphocyte Count; Female; Health Education; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Pilot Projects; Questionnaires; Risk Reduction Behavior; Sexual Behavior; South Africa; Unsafe Sex